The Influence of Games and Intelligences to Ability in Mathematics for TK-Bâs Children - Huliyah, Muhiyatul (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
This article reported the result of research for the influence of games and intelligences to ability in mathematics for TK-Bâs children. The research was held in TK/RA Daarul Muqimien of Buaranjati village, Sukadiri subdistrict, Tangerang regency. The amount of sample are 40 TK-Bâs children. The method used was experimental with 2x2 factorial design. The results of this research are : (1) there was non significant difference to ability in mathematics for TK-Bâs children who given by Monopoly game and TK-Bâs children who given by Snakes-Ladders game; (2) there was non significant difference to ability in mathematics for TK-Bâs children with high intelligence who given by monopoly game and Snakes-Ladders game; (3) ability in mathematics for TK-Bâs children with low intelligence who given by Monopoly game lower than children who given by Snakes-Ladders game; (4) there was significant influence of interaction between games and intelligence to ability in mathematics for TK-Bâs children. Both monopoly game and Snakes-Ladders game could improve the ability in mathematics for TK-Bâs children.